Constraints on the Abundances of Carbon and Silicon in Mercury's Core From Experiments in the Fe‐Si‐C System. Issue 5 (15th May 2020) - Vander Kaaden, Kathleen E.; McCubbin, Francis M.; Turner, Amber A.; Ross, D. Kent
Abstract: The composition of a planet's core has important implications for the thermal and magmatic evolution of that planet. Here, we conducted carbon (C) solubility experiments on iron‐silicon (Fe‐Si) metal mixtures (up to 35 wt% [~52 atom%] Si) at 1 GPa and 800–1800°C to determine the carbon concentration at graphite saturation (CCGS) in metallic melt and crystalline metal with varying proportions of Fe and Si to constrain the C content of Mercury's core. Our results, combined with those in the literature, show that composition is the major controlling factor for carbon solubility in Fe‐rich metal with minimal effects from temperature and pressure. Moreover, there is a strong anticorrelation between the abundances of carbon and silicon in iron‐rich metallic systems. Based on the previous estimates of <1–25 wt% Si in Mercury's core, our results indicate that a carbon‐saturated Mercurian core has 0.5–6.4 wt% C, with 6.4 wt% C corresponding to an Si‐free, Fe core and 0.5 wt% C corresponding to an Fe‐rich core with 25 wt% Si. The upper end of estimated FeO abundances in the mantle (up to 2.2 wt%) are consistent with a core that has <1 wt% Si and up to 6.4 wt% C, which would imply that bulk Mercury has a superchondritic Fe/Si ratio. However, the lower end of estimated FeO (≤0.05 wt%) supports CB chondrite‐like bulk compositions of Mercury with core Si abundances in the range of 5–18.5 wt% and C abundances in the range of 0.8–4.0 wt%. Plain Language Summary: The composition of a planet's core can provide clues as to how the planet has changed over time. In this study, we conducted experiments at high pressures and temperatures to investigate potential carbon and silicon abundances in the core of Mercury. We utilized a variety of iron‐silicon metal mixtures (up to 35 wt% silicon) and graphite capsules in order to examine the concentration of carbon in metallic melts and crystalline metals at graphite saturation with the intention of constraining the carbon and silicon content of Mercury's core. Combining the results of this study with those in the literature, we found that composition is the major controlling factor of carbon solubility in silicon‐bearing, iron‐rich metal, with minimal effects from temperature. More importantly, our results showed a strong anticorrelation between the abundances of carbon and silicon in iron‐rich metallic systems. Since Mercury may have formed in a region of the solar system with less oxygen available, it is likely that some silicon partitioned into Mercury's core as silicon becomes more siderophile under reducing conditions. These findings, when combined with other elemental data, can be used to place constraints on the bulk composition of Mercury, which could help to constrain its origin. Key Points: Composition is the main control of carbon concentration at graphite saturation in Fe‐rich metal, with minimal effects from temperature and pressure Mercury requires ≥27 wt% Si and ≤0.5 wt% C in its core if it has a bulk EH chondritic composition Mercury requires 5–18.5 wt% Si and 0.8–4.0 wt% C in its core if it has a bulk CB chondritic composition